Vibration Analysis Of The Chenderoh Dam Structure Due To The Effects Of Water Spilling And Surging - Ghazali, Mohamad Hazwan Mohd (2019)
Dam structure has to be inspected regularly in order to monitor its reliability due to the effect of flow-induced vibration. Vibration induced by the fluid (water) on the dam structure can lead to the catastrophic failure if the natural frequencies coincide with the frequencies of the water flow. In this research, the effects of water spilling and surging to the Malaysian Chenderoh Dam in terms of vibration are studied. For this purpose, only spillway and intake sections of the Chenderoh Dam are taken into consideration. Modal and Harmonic Analyses are carried out using ANSYS software version 18.2 (ANSYS 18.2) to determine the dynamic characteristics of the dam structure. Next, fluid-structure interaction (FSI) simulation study is conducted and the Operational Deflection Shapes (ODS) from the effect of flow-induced vibration are compared with the natural frequencies and mode shapes of the dam structure. From the results, the natural frequencies obtained for spillway and intake sections are 5.09 Hz and 2.76 Hz respectively. The FSI analysis produced the operating frequency of 4.71 Hz for Case 1 and 7.45 Hz for Case 2-4 of spillway section. This indicates that there is no resonance phenomenon during the operating condition of the spillway. However, resonance phenomenon may occurred for the Case 3 of intake section where the forcing frequency from the FSI analysis (2.35 Hz) coincides with the natural frequency of the intake section. This means that the intake is considered unsafe for this operational condition. Thus, a proper closing procedure for both gates should be conducted to avoid any failure to the structure.